A Comparative Study on Laplace Solutions of Ordinary Differential Equations between Analytical and Matlab Approach - Thamizhsudar, M; K.Bhuvaneswari, A (International Journal of Engineering and Technology, 2018)
The aim of this paper is to give the Laplace solutions of ordinary differential equation through Matlab. Such a solution can be obtained effectively, through the strong knowledge on mathematical way of obtaining the solution of differential equation by applying Laplace transform technique and hence the paper contains both the approaches of analytical as well as by using the software Matlab of Lapalce solutions of differential equations. Â Also this paper provides the codlings to be used to execute the Laplace solutions graphically by which one can Â get the clear understanding of nature of the given problem and be able to interpret the results obtained.Â Â